Kekuatan Lengan dan Keseimbangan Terhadap Kemampuan Handstand Atlet Daradaeng Gymnastic Club - Asri, Ariana; Suparman, Suparman; Haeril, Haeril (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2021)
This study aims to determine the relationship between arm strength and balance on handstand ability. This research is descriptive with two independent variables, namely arm strength and balance with one dependent variable, namely handstand ability. The sample of this research is the athletes of the Makassar Daradaeng Gymnastics Club as many as 20 people. The data analysis technique used is descriptive analysis, correlation coefficient analysis at a significant level of 0.05, using computer assistance through the SPSS program. The results showed: (1) There was a significant contribution between arm strength and Handstand ability, namely Daradaeng Gymanstic Club Makassar athlete with an R Squares value of 0.758 (2) There was a significant contribution between balance and Handstand ability of Daradaeng Gymanstic Club Makassar athlete with an R value. Squares of 0.758 (3) There is a significant contribution between arm strength and balance together with the Handstand ability of Physical Education students with a value (R) of 0.852 and an Fcount (F) of 48.816